2016
DOI: 10.1021/acs.est.6b04647
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Reveals Cryptic Interactive Effects of Species Interactions and Environmental Stress on Nitrogen and Sulfur Metabolism in Seagrass

Abstract: Eutrophication of estuaries and coastal seas is accelerating, increasing light stress on subtidal marine plants and changing their interactions with other species. To date, we have limited understanding of how such variations in environmental and biological stress modify the impact of interactions among foundational species and eventually affect ecosystem health. Here, we used metabolomics to assess the impact of light reductions on interactions between the seagrass Zostera marina, an important habitat-forming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 65 publications
5
39
1
1
Order By: Relevance
“…The close agreement between the amount of available C and that incorporated into growth suggests that assimilation of NH4+ was the major process by which NH4+ was removed since the C contained in synthesized amino acids and proteins were included in our estimate of C allocated to growth. Our findings are supported by data from Castorani et al () and Hasler‐Sheetal et al () who found that eelgrass exposed to high light and high availability of NH4+ (excreted from mussels) had sufficient energy to accumulate amino acids and grow well for about 4 weeks although the C‐reserves became depleted by the end.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The close agreement between the amount of available C and that incorporated into growth suggests that assimilation of NH4+ was the major process by which NH4+ was removed since the C contained in synthesized amino acids and proteins were included in our estimate of C allocated to growth. Our findings are supported by data from Castorani et al () and Hasler‐Sheetal et al () who found that eelgrass exposed to high light and high availability of NH4+ (excreted from mussels) had sufficient energy to accumulate amino acids and grow well for about 4 weeks although the C‐reserves became depleted by the end.…”
Section: Discussionsupporting
confidence: 90%
“…High mobilization of C reserves combined with high acquisition of C resulted in the highest quantity of available C among all 2‐factor treatments. The amount of C allocated to growth constituted however less than 50% of the available C. We know of no studies that have evaluated the processes underlying the combined response to elevated heat and N, but we suggest that the remaining 50% of the available C was allocated to protection and repair processes in an attempt to alleviate the negative effects of HT (e.g., Bergmann et al ; Winters et al ; Gu et al ) while at the same time a significant amount of energy and C must have been used for assimilation of NH4+ since these plants received the same N content as in those from the HN treatment (Marschner ; Villazán et al ; Hasler‐Sheetal et al ). The respiration rate in plants from the HT + HN treatment was similar to that in the control so any additional energetic expenditure related to these processes must either have taken place earlier in the experiment, or plants may alternatively have undergone structural alterations that could serve to reduce respiratory losses at the plant level.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Na, Mg, P, K, Ca, Zn, Mn, Fe, Al, Cu, Mo, and Ag were analyzed using inductively coupled plasma mass spectrometry (ICP-MS 7900, Agilent). The standard solution was diluted from an ICP-MS environmental calibration standard (Agilent), which contains 1000 mg/L each of Fe, K, Ca, Na, Mg, and 10 mg/L each of Ag, Al, As, Ba, Be, Cd, Co, Cr, Cu, Mn, Mo, Ni, Pb, Sb, Se, Tl, V, Zn, Th, and U in 10% HNO 3 .…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Some metabolites that play protective roles in abiotic or biotic stress responses were found more abundant in lettuce leaves exposed to Cu(OH) 2 nanopesticide. More recently, using gas chromatography− qualitative time-of-flight mass spectrometry (GC−qTOF-MS)-based metabolomics, Hasler-Sheetal et al 3 revealed cryptic metabolic changes of seagrass (Zostera marina) and bivalve interactions under reduced-light conditions, which could not be detected by traditional approaches. Thus, metabolomics can provide a more-sensitive and mechanistic understanding of biological response to a particular stressor.…”
Section: ■ Introductionmentioning
confidence: 99%